IP3R-mediated calcium release promotes ferroptotic death in SH-SY5Y neuroblastoma cells - Campos, Joaquín; Gleitze, Silvia; Hidalgo, Cecilia; Núñez, Marco T. (Antioxidants, 2024)
Ferroptosis is an iron-dependent cell death pathway that involves the depletion of intracellular glutathione (GSH) levels and iron-mediated lipid peroxidation. Ferroptosis is experimentally caused by the inhibition of the cystine/glutamate antiporter xCT, which depletes cells of GSH, or by inhibition of glutathione peroxidase 4 (GPx4), a key regulator of lipid peroxidation. The events that occur between GPx4 inhibition and the execution of ferroptotic cell death are currently a matter of active research. Previous work has shown that calcium release from the endoplasmic reticulum (ER) mediated by ryanodine receptor (RyR) channels contributes to ferroptosis-induced cell death in primary hippocampal neurons. Here, we used SH-SY5Y neuroblastoma cells, which do not express RyR channels, to test if calcium release mediated by the inositol 1,4,5-trisphosphate receptor (IP3R) channel plays a role in this process. We show that treatment with RAS Selective Lethal Compound 3 (RSL3), a GPx4 inhibitor, enhanced reactive oxygen species (ROS) generation, increased cytoplasmic and mitochondrial calcium levels, increased lipid peroxidation, and caused cell death. The RSL3-induced calcium signals were inhibited by Xestospongin B, a specific inhibitor of the ER-resident IP3R calcium channel, by decreasing IP3R levels with carbachol and by IP3R1 knockdown, which also prevented the changes in cell morphology toward roundness induced by RSL3. Intracellular calcium chelation by incubation with BAPTA-AM inhibited RSL3-induced calcium signals, which were not affected by extracellular calcium depletion. We propose that GPx4 inhibition activates IP3R-mediated calcium release in SH-SY5Y cells, leading to increased cytoplasmic and mitochondrial calcium levels, which, in turn, stimulate ROS production and induce lipid peroxidation and cell death in a noxious positive feedback cycle.